Prospective study of the relation between landing biomechanics and jumper`s knee - van der Worp, H.; van der Does, H. T. D.; Brink, M. S.; Zwerver, J.; Hijmans, J. M. (International Journal of Sports Medicine, 2016)
The literature on the relation between jump biomechanics and jumper`s knee indicates that a jump with horizontal displacement poses a threat for developing jumper`s knee. Subjects with jumper`s knee have been shown to display a stiff landing pattern characterized by a small range of motion. However, up to now only cross-sectional studies have been conducted. 6 teams from sports involving repetitive landing were followed prospectively for 2 years. At baseline athletes performed the Landing Error Scoring System jump and 3D kinematics and kinetics were obtained. A comparison was made between subjects who developed jumper`s knee and those who did not develop it. 3 subjects developed jumper`s knee during the study. Leg stiffness during landing was high compared to the mean of the healthy controls. No common kinematic patterns could be identified in these 3 subjects. The results suggest that athletes with high leg stiffness during landing might have an increased risk for developing jumper`s knee, yet this conclusion is based on a very small sample. Subjects who develop jumper`s knee do not show a common landing technique. Further research is needed to investigate whether leg stiffness can be used to identify athletes at risk and as a target variable to be used in prevention.